Mirror and replica: A socio-legal proposal to restore the face of Mexico - Ortega-Villaseñor, Humberto (2017)
This research is borne out of a concern for the need to integrate indigenous rights in Mexico so as to enable the peaceful coexistence of the institutions of Mexican positive law and the legal systems of the 62 indigenous peoples living in the country. It is based on the recognition of Mexico as a multiethnic and multicultural society and on the importance of the human rights of its native peoples, as recognized through the reform of articles 1 and 2 of the Constitution of 2001 and 2011. This paper proposes regulatory legislation as an indispensable means of preserving the cultural heritage of Mexico and intercultural dialogue.